Cost-effectiveness of the addition of sintilimab as a first-line therapy for locally advanced or metastatic oesophageal squamous cell carcinoma: a Chinese healthcare system perspective - Cuicui Yu; Yingqi Wu; Yadi Geng; Hui Yan; Pengli Zhu; Peng Ji; Fei Wu; Lijuan Ning; Yubin Feng; Aizong Shen (Health Economics Review)
Abstract Background The ORIENT-15 double-blind randomized controlled trial demonstrated that the addition of sintilimab to chemotherapy for locally advanced or metastatic oesophageal squamous cell carcinoma (OSCC) resulted in better clinical outcomes. In this analysis, we sought to evaluate the cost-effectiveness of sintilimab as a first-line treatment for locally advanced or metastatic OSCC from a healthcare system perspective in China. Methods A partitioned survival model was constructed to perform a cost-effectiveness analysis comparing chemotherapy alone with sintilimab for locally advanced or metastatic OSCC patients. Clinical data were obtained from the ORIENT-15 trial and extrapolated to 10 years. Health state utilities and costs were sourced from the literature and from public healthcare institutions. The primary outcomes included the incremental cost-effectiveness ratio (ICER) and quality-adjusted life-years (QALYs). Two different sensitivity analyses, one-way and probabilistic, were performed to assess model uncertainty. Results Sintilimab-based chemotherapy was more costly ($31699.21 vs. $20687.42) and more effective (0.74 vs. 0.53) than placebo-based chemotherapy, resulting in an ICER of $51908.19 /QALY, which is greater than the willingness-to-pay (WTP) threshold of China ($38223/QALY). Sensitivity analysis demonstrated that the PFS and cost of sintilimab were the major influencing factors affecting the results. Conclusions In patients with locally advanced or metastatic OSCC, sintilimab chemotherapy could improve survival time and health benefits compared with traditional chemotherapy, but the present analysis suggests that sintilimab is not a cost-effective treatment option in China.